Representation of Mental Health Issues in the Film Sleep Call (John Fiske's Semiotic Analysis) - Razzak, Muhammad Ibnu; Prihandoyo, Windi Baskoro (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Abstract: A film is a complex form of mass media. The film Sleep Call provides an overview of mental health issues. Mental health is an important aspect of realizing comprehensive physical and spiritual health. The representation of depression and hallucinations in the film Sleep Call is an attempt to re-understand reality, which cannot be separated from various social issues that are currently developing in society. This research employs a descriptive-qualitative approach and applies John Fiske's semiotics method to analyze the Sleep Call film. The findings of this study demonstrate that John Fiske's semiotic theory, which employs three levels of television codes, specifically the reality level, clarifies Dina's mental health issues stemming from her imprisonment in a challenging and solitary existence. At the representation level, Dina's House is the only location where sets are used, and shooting techniques include long shot, medium shot, high angle, eye level, and slanted shots. At the ideological level, we have the materialism ideology, which places a higher value on material possessions over common sense. . Dina chose to borrow money from an illegal online loan without thinking about the future consequences.